The Surkhan Oasis is an Excellent Attribute of the Face (Juz) in the Construction and Decoration of Housing (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article talks about the modernization of local aspects in the furnishing and decoration of houses. In the late 19th century, the most widespread of permanent housing in southern Uzbekistan was the oat. The kilns, gulls, and hundreds (juzs)living in the region were housing until the 1930s, when after World War II residents began to build housing in Joppa.